Enhancing teachers’ instructional skills through mentorship experiences - Titiworada Polyiem; Prasart Nuangchalerm; Pongthorn Asawaniwed (Journal of Education and Learning (EduLearn), 2026)
Mentorship programs have emerged as a vital support system for new teachers’ professional development. This study developed and evaluated a structured mentoring process to enhance instructional skills among novice teachers. Using mixed-methods research, the researchers examined 97 teachers from 15 disciplines who participated in a local teacher development project in Thailand. The mentoring process incorporated four key components: professional learning teams, collaborative teaching design, mentored practice, and reflective exchange. Quantitative results showed significant improvement in teachers’ instructional capabilities, with overall assessment scores increasing. Qualitative findings revealed that mentorship enhanced abilities in student analysis, lesson planning, and teaching implementation. The study demonstrates that systematic mentorship effectively develops new teachers’ pedagogical competencies while fostering professional growth through collaborative learning.